Quero Amar, Amar de Outra Forma: Restructuring relationships in Lusophone women's poetry - Kirkby, Lorna (2021)
This thesis compares representations of relationships in Portuguese-language poetry written by women. Looking at poetry written by Ana Luísa Amaral from Portugal, Ana Branco from Angola, and Conceição Evaristo and Adélia Prado from Brazil, this study considers how alternatively structured relationships can be represented in poetry in order to rethink gender relations. In doing so, this thesis builds upon existing scholarship on women’s writing and gender representation by bringing together writers from Portugal, Angola and Brazil, considering both how relationships have become the basis for problematic definitions of gender roles in different ways across the Lusophone world, and how they can be rewritten in order to reconceptualise the role of women in different societies. In addition to this, the poetry selected for this thesis underlines the link between human relationships and our understanding of voice and subjectivity, highlighting how paternalist representations of relationships are tied to both the alienation of women and restrictive notions of both literary authorship and poetic subjectivity. By analysing poetic representations of maternal, mystic and amorous relationships, then, this study explores how, by restructuring relationships and representing them otherwise (de outra forma), it is possible to deconstruct restrictive and binary notions not only of gender relations, but also of subjectivity and authorship.